The Role of Cultural Diversity in Geographical diffusion of Hepatitis among Gender in Rural Extents of District Larkana, utilizing the Health Digital GIS Technology - Abbasi, Naila Parveen (Annals of Human and Social Sciences, 2023)
Hepatitis is a burning health issue in rural community of Sindh particularly in district Larkana where dearth of medical remedy in villages/Deh of study area. The culture diversity reflects the gender discrimination in cure for this alignment due to dominant cultural elements, the number of male and female remained change, the high rate in male as compare to female due to the mobility in environment for male disease ratio and female cases not properly reported at the cure sites in study area. This study explored the rate of disease in 2010 to 2016 on the basis of gender difference among male and female on Deh wise in district Larkana. For this the Geoinformatics techniques remained helpful to sort out the disease pattern of gender gap in sited area where the social diversity reflects the living standards among different culture in study area.